Antagonistic Effect of Nitrogen Fertilizer and Rhizobium on Growth, Nodulation and Yield of Peanut (Arachis hypogaea L.) in Acidic Soil - Desy Setyaningrum; Supriyono Supriyono; Riza Noermala Putri (PLANTA TROPIKA, 2025)
Acid soil is widely distributed in Indonesia but underexploited for agriculture due to limited nitrogen availability and aluminium toxicity. Nitrogen fertilizer and rhizobium are crucial to improving plant growth, especially in peanut cultivation. This study examines the antagonistic effects of nitrogen fertilizer and rhizobium on the growth, nodulation, and yield of peanuts cultivated in acidic soil. A factorial randomized complete block design with two factors: nitrogen fertilizer application (0, 50, 100, 150 kg ha-1) and rhizobium inoculation (without rhizobium, rhizobium at 10 g kg-1 seed, and rhizobium sourced from peanut plantations). The combination of 100 kg ha-1 nitrogen and rhizobium from peanut plantations resulted in the highest leaf count (675.33 leaves per plant). A nitrogen dose of 50 kg ha-1 produced the highest effective number of nodules and total nodules. The optimum nitrogen fertilizer dose is 44 kg ha-1 for nodule growth. 50 kg ha-1 nitrogen dose produced the highest number of pods and seed weight, namely 48.67 pods and 407.79 g of seeds. These findings suggest that when applied at an appropriate dose, nitrogen fertilizer enhances peanut growth, nodulation, and yield in acidic soil. However, excessive nitrogen application may induce antagonism with the nodulation process, reducing overall yield.